THE EKO-TEOCRACY CONCEPT IN DISPOSAL SETTLEMENT OF OIL POLLUTION IN THE SEA BY TANKER SHIP - Purwendah, Elly Kristiani (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2019)
The shift in the Eco-Theocratic thinking in resolving oil pollution disputes at sea by tankers is intended as a new paradigm reconstruction that is more oriented to deep ecology with an ecoliteracy perspective towards a new ecodesign environment as an equal subject to human beings resisting anthropocentrism toward society sustainable sociaty and sustainable environmental development. This concept was built through an analysis of the shift in the perspective of philosophical figures from the organic paradigm of nature to the mechanistic paradigm of new nature and paradigms in looking at nature systemically, holistically and ecologically. This new ecoliteracy paradigm is analyzed through a system of democracy, ecocracy and theocracy with a measure of theology and paradigm of the Pancasila.